Colour Doppler and Volume Changes—Anterolateral Thigh Flap: The Sunnybrook Experience. (3rd November 2011) - Eskander, Antoine; Enepekides, Danny; Higgins, Kevin
Abstract : This paper summarizes two recent ALT studies from our institution focusing on the utility of colour flow Doppler's ultrasonography and volumetric changes with radiation. Lastly, we will discuss recommended changes to practice due to the aforementioned studies. Our findings suggest that special care should be made to identify patients at high risk for peripheral arterial disease, and, if the reconstructive surgeon has any concerns, preoperative colour flow Doppler's ultrasonography should be undertaken to better characterize the perforator anatomy and avoid inappropriate flap elevation in patients with silent claudication. Particular detail should be paid to flap thickness especially in patients with increased body habitus. Radiation therapy has on average 20% flap volume-reducing effect, and an overestimation of volume in patients who will be undergoing radiotherapy should lead to the best contour and cosmetic outcomes.